2021
DOI: 10.1097/gox.0000000000003493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Surgical Decision-making in Nonsyndromic Sagittal Craniosynostosis Using a Digital 3D Model

Abstract: Background: Surgical correction of craniosynostosis addresses potentially elevated intracranial pressure and the cranial deformity. In nonsyndromic sagittal synostosis, approximately 15% of patients have elevated intracranial pressure. The decision to operate therefore likely reflects a combination of aesthetic goals, prevention of brain growth restriction over time, surgeon training and experience, and parental expectations. This study examines clinical factors that influence surgical decision-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is crucial in examining the significant variation in the methods by which craniofacial surgeons decide whether to operate on a particular patient with craniosynostosis. 31,32 A major limitation of implementing standardized protocols is the lack of objective quantification of severity. The Whitaker classification has been the accepted standard for aesthetic outcomes reporting in craniosynostosis research, [33][34][35][36] but has been shown to have low interrater reliability and cannot predict the need for future interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is crucial in examining the significant variation in the methods by which craniofacial surgeons decide whether to operate on a particular patient with craniosynostosis. 31,32 A major limitation of implementing standardized protocols is the lack of objective quantification of severity. The Whitaker classification has been the accepted standard for aesthetic outcomes reporting in craniosynostosis research, [33][34][35][36] but has been shown to have low interrater reliability and cannot predict the need for future interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical factors are considered, including patient age, comorbidities, type and severity of craniosynostosis, surgeon training and experience, aesthetic goals, future neurologic complications, and patient family preference. 32 Furthermore, there are variations in the type of surgery offered to particular patients—open techniques, which have been the standard of care for several decades, and more recently developed minimally invasive techniques. 38 There is currently no agreed-on objective method that contributes to surgical decision-making in the management of patients with craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical impact of having accurate head shape classification tools available to medical providers was highlighted by Hughes et al, who recently demonstrated that the severity of the head shape is the most significant factor in determining whether surgeons recommend surgical treatment for a patient with sagittal craniosynostosis. 23 Historically, CI has been used to quantify the severity of scaphocephalic head shapes, but some groups have noted that the use of CI can lead to underreporting of the severity of sagittal craniosynostosis in some patients due to the anterocaudal displacement of the euryon in these cases. 24,25 The appropriateness of relying on the CI was also studied by Fearon et al, who determined that although the average preoperative CI was below normal among patients with sagittal craniosynostosis, 87.5% of patients had measurements that fell within 2 standard deviations of the mean.…”
Section: Discussionmentioning
confidence: 99%
“…An utmost scrutiny to decide whether or not the patient is a candidate with features of raised intra cranial pressure for emergent surgical intervention is accomplished. 4 CT scan of the head and three dimensional reconstruction using both bone and soft tissue windows is the investigation of choice. An auxiliary CT venogram can be done if a suspicion of abnormal venous drainage is speculated.…”
Section: Preoperative Evaluationmentioning
confidence: 99%